Implementing a Rapid Improvement Event with anonymised individual performance reporting on benign hysterectomy care: a retrospective comparative analysis - Hairil Rizal Abdullah; Celestine Loh; Jason Shau Khng Lim; Yang Lv; Jia Xuan Yeo; Rhoda Su Hui Lew; Xu Ying Leow (BMJ Open Quality)
Introduction Value-Based Healthcare (VBHC) aims to enhance patient outcomes while managing costs. Building on VBHC principles, the Ministry of Health Singapore introduced the Value-Driven Care programme, including initiatives like Enhanced Recovery After Surgery and Patient Blood Management. However, clinical quality remained suboptimal despite these measures due to limited clinician performance transparency. To address this, the Office of Value-Based Healthcare led a Rapid Improvement Event that implemented Individual Clinical Reports (ICRs) to provide clinicians with performance feedback. This study hypothesises that an active feedback loop using ICRs, combined with regular departmental dashboard reviews, would improve clinical quality, measured by the Clinical Quality Index (CQI).Methods A quasi-experimental design compared pre-ICR and post-ICR implementation data, analysing improvements using Fisher’s exact tests and logistic regression. Adjustments were made for multiple variables such as comorbidities, surgery type and American Society of Anesthesiologists classification.Results ICR implementation significantly improved CQI performance (p=0.013) and reduced blood transfusion (p=0.046). Secondary outcomes, including length of stay, complications and readmission rates, also showed improvements with trends towards significance.Conclusion An active feedback loop consisting of ICRs and multidisciplinary team discussions enhanced CQI for hysterectomy patients at a tertiary hospital in Singapore. They represent a valuable feedback tool with the potential to improve care quality in other standardised surgeries.